EPIDEMIOLOGY OF SUICIDE IN FAISALABAD - Saeed, Ahmad; Bashir, M. Zahid; Khan, Delawar; Iqbal, Javed; Raja, Khurram Sohail; Rehman, Anayatur (Journal of Ayub Medical College Abbottabad, 2002)
Background: Suicide is one of the ten leading causes of death in the world, accounting for more than 400,000 deaths annually. The incidence and pattern of suicide vary from country to country. Cultural, religious and social values play some role in this regard. Very few studies about the epidemiology of suicide have been conducted in Pakistan. We conducted this study on the patterns of suicide in autopsies conducted at Faisalabad from 1998 to 2001, to know the incidence of suicide, which subgroups of the population were most vulnerable to such deaths and the methods being used. Materials and Methods: The study includes 95 cases of suicidal deaths of both sexes belonging to different age groups autopsied at the Department of Forensic Medicine, Punjab Medical College, Faisalabad. Cases were selected on the basis of information from the scene of crime, police inquest, autopsy findings and interview with the acquaintances of the victim. Findings were tabulated and analyzed. Results: The study revealed that suicide rate was 1.12/100,000, with male preponderance. The peak incidence was in 20-29 years in males and 10-19 years in females. Hanging was the most common method. A seasonal surge in spring was noted. Conclusion: Suicide in Faisalabad is much lower compared to western countries. Suicides occur at a younger age in Faisalabad compared to western countries. KEY WORDS: Suicide, Firearms, Seasonal variation.